Developing IPAS Teaching Materials with an Integrated Deep Learning Approach and Character Values to Improve Elementary Students’ Critical Thinking Skills - Sunarsi, Sunarsi; Yaumi, Muhammad; Rasyid, Nur Akbar; Rosdiana, Rosdiana (PPSDP International Journal of Education, 2025)
This study aims to develop Natural and Social Sciences (Ilmu Pengetahuan Alam dan Sosial/IPAS) teaching materials using a deep learning approach integrated with core character values to strengthen elementary students’ critical thinking skills. Employing a Research and Development design based on the ADDIE model, the study involved needs analysis through surveys of 100 teachers and 200 students across five elementary schools in Central Java, which revealed weaknesses in existing materials, particularly the lack of interactivity and moral content. The teaching materials were designed as project-based modules incorporating virtual simulations, case studies, and collaborative tasks that embed topics such as ecosystems and social dynamics with values of honesty, responsibility, and cooperation. The intervention was implemented in an experimental class of 50 fifth-grade students, compared with a control group using standard materials. Results showed a significant improvement in critical thinking, with students’ HOTS-based test scores increasing from 65% to 85% (p < 0.05, medium effect size). Qualitative observations also indicated enhanced cooperative and ethical behavior among 80% of students. Expert validation yielded a high feasibility rating (M = 4.5/5). The findings demonstrate that integrative deep learning–based IPAS materials can effectively advance both cognitive mastery and character formation, offering a holistic alternative to traditional instruction. This study contributes a validated, scalable model for strengthening critical thinking and character education, supporting broader adoption in the Indonesian national curriculum.